Strategi Manajemen Pusat Sumber Belajar Dalam Meningkatkan Efektivitas Pembelajaran Berbasis Metode Blended Learning - Hayati, Puspa Indah; Desriani, Rospita; Dewi, Sintia; Arumsari, Tania; Widiyan, Tika (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This study aims to analyze the management strategy of the Learning Resource Center in supporting the effectiveness of blended learning-based learning. This research uses a library research method by collecting data from various literature such as books, scientific journals, and relevant previous research results. The results of the study show that the Learning Resource Center has a strategic role in providing digital facilities, managing educational resources, and integrating technology into the learning process. Effective management strategies include developing technological infrastructure, improving educators' competencies in the use of digital media, and aligning learning content with curriculum needs. With structured and adaptive management, Learning Resource Centers can be a key factor in increasing the effectiveness and sustainability of the implementation of blended learning in educational institutions.